STRATEGIC ANALYSIS OF THE EFFICIENCY OF ONLINE RETAIL BUSINESS MODELS - Касич, Алла О. (Journal of Strategic Economic Research, 2025)
The article examines the processes of development of e-commerce, which is carried out in various forms and forms through the use of digital technologies. The development of digital technologies and the increase in trade volumes become the basis for the formation and dynamic growth of e-commerce. The review of scientific sources allowed us to identify relevant areas of research into the processes of development of e-commerce, including the issue of improving business models. Based on the analysis of the main indicators characterizing the development of e-commerce in the world, the main trends were identified. The growth of e-commerce is taking place at a relatively high pace. As the analysis showed, the growth of the retail sales market using digital technologies is expected to continue in the future. A number of factors related to the development of the economy will contribute to this. A list of key factors for the development of online shopping was also identified, which analysts call: convenience, wide access, economic efficiency, improved logistics, mobile accessibility of purchases. It was noted that different types of business models are formed based on the interaction of three groups of parties, private business, state administrations and consumers. The main characteristics of business models were also given. It was emphasized that there are six types of e-commerce models: intermediary, advertising, "direct", trade, information and subscription. To conduct a strategic analysis of e-commerce business models, a list of key indicators was proposed, which are traditionally used in the research process and which take into account the specifics of the development of e-commerce.